Development of Smart Adventure Games to Improve the Readiness of the Initial Ability of Reading, and Writing (CALIS) on Early Childhood - Linda Dwiyanti; Rosa Imani Khan; Epritha Kurniawati (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
Based on these circumstances, this study aims to develop an appropriate game to improve readiness of the initial ability of reading, and writing on early childhood called "Smart Adventure". This game can help children to learn the ability of the initial reading and writing with a fun method (play) and in accordance with the characteristics and stages of early childhood development. This study used a qualitative and quantitative approach (mix method) with "Borg and Gall" research and development model. The procedures used include: research and information collecting, planning, develop preliminary form of product, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, and dissemination and implementation.The results of this study indicate the effectiveness and usefulness of the Smart Adventure game product on the ability to reading and writing early childhood